التعلم التعاوني وإرهاصاته عند علماء التربية المسلمين: THE COOPERATIVE LEARNING AND ITS INDICATIONS AMONG MUSLIM EDUCATIONAL SCHOLARS - Bamba, Adama; Mohd Yusoff, Mohd Yakub @ Zulkifli; Yussuf, Ahmad (Journal of Islamic Educational Research, 2017)
This paper aims at pondering into the 'Cooperative Learning' strategy origins in the Muslims' educational culture. To achieve this objective, this paper has followed an analytic method. It was found, based on the reading of some classical texts of Ibn Sina, al-Zarnuji and Ibn Jama'ah, that Muslim educational scholars were deeply aware of the significance of the Cooperative Learning which is considered nowadays as one of the important approaches in teaching and learning. It is believed that children learn better from each other that they do in learning with their teachers and adults. However, due to the limitations of this paper, it is hoped that further researches would be more elaborated to include more evidences and materials in studying the origins of the Cooperative Learning in Muslims' educational tradition.